Adventures With Mommsen - Brian Croke (History of Classical Scholarship)
Theodor Mommsen (1817–1903) has long been considered the greatest Roman historian of the nineteenth century. Above all he was an accomplished philologist, editor and scholarly organiser. This paper provides one historian’s reflections on decades of engaging with Mommsen in various contexts and in various places. It traces a personal encounter with Mommsen and his work, especially his activities in later Roman history, from undergraduate through postgraduate education, a four-decades long career outside academia, then a return to Mommsen in recent years. These various adventures with Mommsen demonstrate how much the business of doing research and writing about any individual or topic has changed especially in the last thirty years. Essentially autobiographical in approach, this paper also highlights both the role and the limits of autobiography in understanding one’s own education and scholarly development.